PEMBELAJARAN BAHASA INGGRIS UNTUK SEKOLAH DASAR MELALUI CERITA RAKYAT ANAK PAPUA - Wigati Yektiningtyas; Budi Rahayu (LPPM Uncen, 2017)
Some Primary Schools in Jayapura, Papua teach English but some teachers still face difficulties in teaching it. Suitable materials and strategies are the obstacles. Inisiative of teaching English using Papua children folktales is used as a scaffolding to help better teaching-learning process. Emphirically, Papua children folktales can be used to teach (1) alphabet, (2) vocabularies, (3) phrases, (4) simple sentences, and (5) numbers. Short drama, songs, and games are inserted to strengthen what the students have learned. The initiative result shows that the teaching process is more interesting and unstressful for the students because the materials are adopted from their natural and socio-cultural environment. Unity of cognitive, affective and psychomotor domains are also involved in the learning process that encourage students to be more active and confident. Keywords: Teaching-learning process, alphabet, vocabularies, phrases